2007
DOI: 10.1002/chin.200735259
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Biological Activities and Synthesis of Kaurane Diterpenes and Their Glycosides

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…Other discriminant metabolites were kaurane diterpenoids such as annoglabasin A (methyl‐16 β ‐acetoxy‐19‐al‐ ent ‐kauran‐17‐oate)/annoglabasin B (16 α ‐hydro‐19‐acetoxy‐ ent ‐kauran‐17‐oic acid). These have been principally reported in fruits of Annona glabra , although they may be present in plant species belonging to several families, including mannic acid, a novel dimeric ent ‐kaurane diterpene identified in various Diospyros mannii tissues . The detection of ursanes such as ursa‐12,18‐dien‐3‐ol, 11‐methylgerberinol, and cinnamyl acetate was congruent with their previous identification in fruits of D. kaki and D. blancoi .…”
Section: Discussionsupporting
confidence: 79%
“…Other discriminant metabolites were kaurane diterpenoids such as annoglabasin A (methyl‐16 β ‐acetoxy‐19‐al‐ ent ‐kauran‐17‐oate)/annoglabasin B (16 α ‐hydro‐19‐acetoxy‐ ent ‐kauran‐17‐oic acid). These have been principally reported in fruits of Annona glabra , although they may be present in plant species belonging to several families, including mannic acid, a novel dimeric ent ‐kaurane diterpene identified in various Diospyros mannii tissues . The detection of ursanes such as ursa‐12,18‐dien‐3‐ol, 11‐methylgerberinol, and cinnamyl acetate was congruent with their previous identification in fruits of D. kaki and D. blancoi .…”
Section: Discussionsupporting
confidence: 79%
“…Kaurane types of cyclized diterpenoids, mostly of the ent-series, are common constituents in traditional herbal remedies. Garcia et al [76] have reviewed in detail the occurrence and biological activities of kaurane diterpenes and their glycosides. Several kaurane diterpenoids are known to inhibit NF-kB signaling and to suppress inflammatory responses.…”
Section: Triptolidementioning
confidence: 99%
“…Namely, the 'normal' series are the structures whose fusion between A and B rings occurs in the same way as in steroids, while the structures of the 'enantiomeric' series (denoted as ent) are the corresponding specular images of the normal series. [18] Furthermore, it has been demonstrated that P450 that are key enzymes in plants, catalyze the three steps of oxidation of ent-kaurene to ent-kaurenoic acid in several plant species (CH 3 !CH 2 OH/kaurenol!CHO/ kaurenal!COOH/kaurenoic acid), as well as the oxidation of (À )-kaurenoic acid to the ent-7-α-hydroxykaurenoic acid. [36 -40] Oxidation of ent-7-α-hydroxykaurenoic acid to the ent-7-oxoderivative was detected in an investigation of gibberellin biosynthesis in bacteria.…”
Section: Resultsmentioning
confidence: 99%